THE INTERPLAY OF FINANCIAL TECHNOLOGY, DIGITAL TRADE, AND ENVIRONMENTAL REGULATIONON SUSTAINABLE ECONOMIC GROWTH IN ADVANCED ECONOMIES - Nageri Kamaldeen (Gusau Journal of Accounting and Finance)
This study investigates the combined effects of fintech readiness, digital trade openness, mineral resource rents, and environmental policy stringency on economic growth across OECD countries from 2000 to 2023. Utilizing the Method of Moment Quantile Regression (MMQR), the analysis reveals heterogeneous impacts across the growthdistribution,wherefintechreadinessanddigitaltradeconsistentlypromotegrowth,whiledependenceon mineral rents tends to constrainit. Environmental policystringencyemerges as a significant positive moderator, indicating that stringent environmental regulations can support sustainable economic expansion without hindering development. These findings highlight the importance of integrating technological innovation, trade facilitation, resource management, and environmental governance in crafting growth policies. The study contributes to the literature on sustainable economic development and digital transformation by providing nuanced insights relevant to policymakers and stakeholders in advanced economies.